City network mining in china’s yangtze river economic belt based on “two-way time distance” modified gravity model and social network analysis - Chai, Duo; Du, Jiaze; Yu, Zongqi; Zhang, Dong (Frontiers in Physics, 2022)
In this paper, the “two-way time distance” modified gravity model is used to integrate the social network analysis method and Arc GIS spatial analysis method. The city network mining method has been improved, and the structural characteristics, causes and laws of city network in the Yangtze River basin of China have been empirically analyzed. The results show that the modified gravity model can better reveal the interaction differences between cities and reflect the current and potential economic, population and resource relations among cities. The city network density of the Yangtze River Economic Belt is positively related to the regional economic development level. The average value of degree centrality in the basin is high, but the difference between cities is obvious. The “agglomeration effect” of the central cities is significant, and the urban connections have an obvious cluster structure, showing an “M” shaped spatial distribution along the Yangtze River; The inner connection strength of city network subgroups is high, but the connection between subgroups is low. The law of “downstream > midstream > upstream” also appears on the closeness centrality and betweenness centrality. In the future, it is necessary to promote the integration of urban agglomerations in the river basin and form a development pattern of “downstream driving - midstream transition - upstream connection”; strengthen the functions and connections of central and sub central cities; and support the development of underdeveloped cities through the persistent mobilization of outstanding officials.